When Health Workforce Requirements Mismatch with Health Workforce Supply: Health Workforce Planning of the Public Health Inspection, Zone 3, Ministry of Public Health - Patanavanichanan, Nattaya; Pagaiya, Nonglak (Journal of Health Science of Thailand, 2017)
The study was aimed at analyzing and projecting health workforce supply and requirement and developing recommendations of health workforce planning of the public health region zone 3, Ministry of Public Health. Checklist for data collection comprising: health workforce distribution and mobility, service utilization, health workforce time allocation and productivity, were developed and used. The health workforce supply and requirements were assessed and forecasted for the next 5 years. The results showed that, besides general doctors, the requirement projection revealed that these following specialist doctors would be in shortages: internal medicine, general surgery, pediatrics, obstetrics/gynecology, anesthetic, orthopedic, otolaryngology, ophthalmology, and neurosurgery, respectively. With regards to others professionals, the health workforce projection had been conducted. Health workforce that would be shortages at both general and community hospitals were: registered nurses, medical technicians, medical technician assistants, Thai traditional medicine personnels and physical-therapists. On the contrary, dentists and dental technician, surplus were likely to be seen. The results suggested that to manage health workforce to be equally distributed, measures need to address as the following were suggested. Firstly, increase the uptake of those professionals who were likely to be shortages. Secondly, increase the utilization of skill mix between professional and supporting staff. Thirdly, improve retention measures to retain health workforce.